PENGARUH CITRA PERUSAHAAN DAN CITRA PEMAKAI TERHADAP KEPUTUSAN PEMBELIAN JASA PERBANKAN SYARIAH DI JEMBER - Saiful Amin; Muhammad Dimyati; Muhammad Firdaus (RELASI : JURNAL EKONOMI, 2016)
Business engaged in the banking industry, need to pay attention to aspects of corporate image and user image. These two aspects, has always been a discussion that is very important in developing the banking business, because of the growth in this business depends on customer confidence in the company that can be created through the corporate image and user image. This study aimed to test the effect of the corporate image and user image on purchasing decisions Islamic banking services in Jember. The population in this study is that people who use services Islamic banking in Jember. Given the large number of population in this study, the sample used was simple random sampling which is used to specify the bank to be sampled and purposive sampling was used to determine the respondent from bank customers was selected. Based on these two methods, the obtained sample of 140 respondents. Methods of data analysis using multiple regression analysis with latent variables with the help of software lisrel 8.72. Based on the results of data analysis showed that the corporate image and user image has significant effect to the purchasing decisions of Islamic banking services in Jember. This result also reveals that the corporate image most dominant influence on purchasing decisions Islamic banking services in Jember.